2019
DOI: 10.1002/hbm.24857
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic changes in the thalamocortical circuit in Parkinson's disease

Abstract: Parkinson's disease is characterized by bradykinesia, rigidity, and tremor. These symptoms have been related to an increased gamma-aminobutyric acid (GABA)ergic inhibitory drive from globus pallidus onto the thalamus. However, in vivo empirical evidence for the role of GABA in Parkinson's disease is limited. Some discrepancies in the literature may be explained by the presence or absence of tremor. Specifically, recent functional magnetic resonance imaging (fMRI) findings suggest that Parkinson's tremor is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 68 publications
(103 reference statements)
0
38
0
Order By: Relevance
“…For patients only, each day started with a measurement of their motor symptoms (using the UPDRS motor scale), followed by administration of medication (or placebo). Next all participants underwent a combination of functional MRI and anatomical scans that lasted ∼2 h ( Dirkx et al , 2019; van Nuland et al ., 2020, submitted for publication ). After a short break, participants performed the behavioural task (outside the scanner).…”
Section: Methodsmentioning
confidence: 99%
“…For patients only, each day started with a measurement of their motor symptoms (using the UPDRS motor scale), followed by administration of medication (or placebo). Next all participants underwent a combination of functional MRI and anatomical scans that lasted ∼2 h ( Dirkx et al , 2019; van Nuland et al ., 2020, submitted for publication ). After a short break, participants performed the behavioural task (outside the scanner).…”
Section: Methodsmentioning
confidence: 99%
“…However, our finding provides strong evidence that the cerebellum should be considered as a primary site for systems-level compensation in the disorder [ 5 ]. Considering the neuroprotective role of GABAergic inhibition [ 51 ], future intervention studies are necessary to test how the modulation of GABAergic mechanisms changes PD cognitive symptoms, and to establish whether GABA plays a compensatory or pathophysiological role in Parkinson’s disease. This is of clinical relevance since pharmacologically boosting GABAergic neurotransmission in PD patients modulates aberrant neuronal network oscillations at beta frequency [ 52 ], which seems to restore cognitive functions, at least in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally thought that bradykinesia results from the loss of dopaminergic neurons in the substantia nigra pars compacta and subsequent striatal dopamine depletion [ 142 ]. However, it has recently been suggested that GABA plays a modulatory role in the pathophysiology of PD that is independent of dopaminergic medication [ 143 , 144 , 145 ]. In addition, the GABA A R/Cl − , HCO 3 − ATPase from rat brain is involved in the phenol-induced manifestations of both head-twitching and tremors [ 94 ].…”
Section: The β3 Subunit and Human Diseasesmentioning
confidence: 99%